The CIMMYT wheat breeding strategies and its relevance to Ethiopia - Abeyo, Bekele G.; Badebo, Ayele (Ethiopian Institute of Agricultural Research, 2022)
Wheat is the most important food security crop globally. Recent world wheat production stand at 766 million tons on 216 million hectares though wheat production is challenged by various biotic, abiotic, and other factors. As a global leader in wheat research, CIMMYT’s primary goal is to develop broadly adapted germplasm with high and stable yield, durable disease resistance, stress tolerance and acceptable end-use quality strategically addressing the different mega-environments such as irrigated regions, high-rainfall areas, acid soils, semiarid zones, tropical areas, and winter wheat zones. CIMMYT’s Global wheat program is one of the most important public sources of high yielding, nutritious, disease resistant and climate-resilient wheat varieties for Africa, Asia, and Latin America. The program works with the International Center for Agriculture Research in the Dry Areas (ICARDA), the CGIAR Research Program on Wheat, and NARS. The CIMMYT wheat breeding program is supported by multidisciplinary team of experts with breeders strategically and internationally located at key regional offices to facilitate germplasm and information exchange as well as technically support NARS. The primary focus of the breeding program is on core (must have) traits with some emphasis on additional traits for specific environments. The center is crossing, selecting, developing, and distributing stable, and high yielding advanced lines which includes some Zn and Fe enriched germplasm, with durable pest resistance, stress tolerance and superior quality using the different strategies, and methods, highlighted. In addition, CIMMYT collaboration with Ethiopian NARS in some areas will also be briefed.